EPIDEMIOLOGICAL STUDY ON THE SPREAD OF CONTAGIOUS SKIN DISEASES IN OVERCROWDED URBAN ENVIRONMENTS: A COMPREHENSIVE ANALYSIS - Kusumawaty, Ira (Lafadz Jaya Publisher, 2025)
The spread of contagious skin diseases in densely populated areas presents a significant public health challenge. This study explores the epidemiology of skin diseases within high-density urban populations, analyzing the contributing factors, transmission dynamics, and preventive strategies. The study was conducted in an urban area with a high concentration of residents, focusing on the most prevalent skin diseases, including scabies, fungal infections, and impetigo. Data was collected through surveys, clinical examinations, and environmental assessments to understand the correlation between overcrowding, hygiene practices, and spread disease. Results indicated a strong link between high population density and the increased incidence of skin infections. Limited access to healthcare, poor sanitation, and lack of public health education were identified as key factors exacerbating the issue. The findings emphasize the importance of early diagnosis, public health interventions, and community education in reducing the transmission of skin diseases. This study provides valuable insights into the epidemiology of contagious skin diseases in urban settings, offering guidance for policymakers and health practitioners in addressing this ongoing issue.